GENDER INEQUALITY UNDER NAZI GERMANY DURING WORLD WAR II IN MARTHA HALL KELLY’S LILAC GIRLS NOVEL - Icha Rizky; Muhammad Fithratullah (Linguistics and Literature Students' Journal, 2023)
Gender inequality is a condition that occurs between men and women in family life, society, nation and state. This abstract aims to provide a brief overview of research that explores Martha Hall Kelly's "Lilac Girls" narrative and analyzes gender inequality during the Nazi colonial period. The novel explains feminist actions that focus on gender inequality that occurs in women and men. The author used qualitative descriptive methods to present data analysis in this study. The data is in the form of excerpts and narratives from the novel Lilac Girls that illustrate a relevant research problem, namely gender inequality. This thesis uses a socio-historical approach to see the relationship between literary works and historical elements of society that occurred in the past. Furthermore, this thesis uses Mansour Fakih's theory of gender inequality. The results of the analysis show that the novel Lilac Girls by Martha Hall Kelly clearly describes gender inequality with four strategies by Mansour Fakih as analysis: subordination, stereotypes, marginalization, violence, and double burden; based on the results of the analysis, the novel Lilac Girls which makes a form of gender inequality bias that occurred during World War II which a group of Nazis controlled.Keywords: Lilac girls, marginalization, nazi colonial, stereotype, violence